Ladies night at the Dreamland - Livingston, Sonja (Crux (Athens, Ga.), 2016)
At the Dreamland, women and girls flicker from the shadows to take their proper place in the spotlight. In this lyrical collection, Sonja Livingston weaves together strands of research and imagination to conjure figures from history, literature, legend, and personal memory. The result is a series of essays that highlight lives as varied, troubled, and spirited as America itself. Harnessing the power of language, Livingston breathes life into subjects who led extraordinary lives-as rule-breakers, victims, or those whose differences made them cultural curiosities-bringing together those who sl.